Assembly Modul Pembaca Transponder RFID dan Pengujiannya - Muhammad Arifin; Nadhrah Wivanius; Creed Ridho Sonsania (Journal of Applied Electrical Engineering, 2023)
Nowadays, development technology is very fast such as Radio Frequency Identification Device (RFID). This RFID technology is very needed. In Indonesia, the most RFID hardware is still bought from other countries especially from Cina. The RFID hardware consists of an RFID transponder and RFID reader module. Some industries or institutions in Indonesia has a chance to produce them both RFID transponder and RFID reader module. In this research focus to manufacture RFID reader module. Manufacturing of RFID reader module has some steps such as drawing the schematic diagram, drawing PCB layout, printing PCB, assembly the components on PCB, and testing. After testing, some data are obtained. The manufactured RFID reader module can successfully read RFID transponder, but this module can only read with the maximum range 7 mm whereas the bought RFID reader module can read more than 7 mm.